2013
DOI: 10.5942/jawwa.2013.105.0098
|View full text |Cite
|
Sign up to set email alerts
|

Is Regulating By Groups More Effective? Or Not?

Abstract: Regulating by groups may be one of these concepts that initially sounded good but starts to fall apart under close scrutiny. We need to ensure that a cVOC Rule increases public health protection and does not imply more effective regulation that cannot be demonstrated. A group regulation should not be developed for the sake of regulating by groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…As with the first approach for establishing a group MCL, this approach may be challenging to implement in everyday practice. As Roberson (2013) described previously, this approach is complicated by a few of the individual compounds being considered, such as 1,2,3‐trichloropropane (TCP), that have substantially higher cancer slope factors than other compounds. If the cVOC regulation is developed around reducing total risk, it may be difficult to establish a total risk framework that is not a de facto TCP regulation.…”
Section: Potential Regulatory Scenarios For Group Cvoc Regulation Devmentioning
confidence: 99%
“…As with the first approach for establishing a group MCL, this approach may be challenging to implement in everyday practice. As Roberson (2013) described previously, this approach is complicated by a few of the individual compounds being considered, such as 1,2,3‐trichloropropane (TCP), that have substantially higher cancer slope factors than other compounds. If the cVOC regulation is developed around reducing total risk, it may be difficult to establish a total risk framework that is not a de facto TCP regulation.…”
Section: Potential Regulatory Scenarios For Group Cvoc Regulation Devmentioning
confidence: 99%
“…It's a good concept in theory. However, in practice, developing a group regulation has been much more challenging than anticipated (Roberson, 2013). The ongoing federal budget issues have likely contributed to the cVOC Rule being delayed into 2015 (and potentially even later).…”
Section: Other Delaysmentioning
confidence: 99%
“…Regarding the cVOC Rule, nothing much new has happened with it other than it's still not completely clear which specific cVOCs are going to be included in the proposed rule in 2014. The cVOC Rule is turning out to be USEPA's first test in regulating by groups, and it's turned out to not be as simple as originally anticipated (Roberson, 2013). Previous research found several differences in physical and chemical characteristics for the cVOCs initially considered for this rule as well as the need for multiple analytical methods (Roth, 2012;Eaton, 2012).…”
Section: Status Of Four Regulatory Actionsmentioning
confidence: 99%